ANALISIS YURIDIS TERHADAP PERJANJIAN PINJAM NAMA SEBAGAI BENTUK KEPEMILIKAN TANAH OLEH WARGA NEGARA ASING - PRATANYA NOVIA ERMIDA (PREMISE LAW JURNAL, 2018)
dosen pembimbing:1. Muhd Yamin2. T. Keizerina Devi A3. Suprayitno Indonesian citizens have equal rights and opportunities to the legal relationship over land, water and air space within Indonesia’s regions. The government also gives opportunities to WNA (foreign citizens) to possess properties in Indonesia; the foreign investors are provided opportunities and chances to put investment in Indonesia under some limitations to their rights such as holding leasehold and lease. Foreign citizens in fact are often dissatisfied with these limitations and still would like to own the land in Indonesia by making a nominee agreement as a form of land ownership, as taking place in the case stipulated in the Denpasar District Court’sVerdict No. 82/PDT.G/2013/PN.DPS.Keywords: A Nominee Agreement, Foreign Citizen, Notary.